The Instituted Ministries of Readers and Acolytes: A Kairos for the Synodality of the Liturgy - François-Xavier Amherdt (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Among the proposals for the implementation of the motu proprio Spiritus Domini and Antiquum Ministerium of Pope Francis (2021), opening the instituted ministries also to women and to lay people not on the way to ordination, the Note of the Italian Bishops’ Conference of June 2022, is certainly one of the most relevant with respect to the discernment, formation and conditions of access of candidates. By receiving a sacramental from the bishop in a community liturgy, for a perennial ministry at the service of the Word of God, the care of the body of Christ in the Eucharist and in the sick, as well as for Christian initiation and small base communities, the instituted ministers can contribute to the synodal revitalization of the ecclesial communion. Decreed ad experimentum for three years, the Italian document can inspire other Bishops’ Conferences around the world.